ANALISIS PEMETAAN POTENSI EKONOMI PONDOK PESANTREN BANGKA BELITUNG - Rahmat Ilyas; Rudi Hartono; Fazlur Rahman Bin Kamsani (Asy Syar'iyyah: Jurnal Ilmu Syariah dan Perbankan Islam, 2023)
Islamic boarding schools, as the oldest traditional Islamic educational institutions, have grown organically and flourished among the Muslim community in Indonesia. One of the current challenges in the modern world is the economic aspect, an integral part of social life that is closely linked to the fulfillment of needs and desires. The economic potential of Islamic boarding schools lies in an economic system based on their strengths, where economic activities are conducted through self-sufficiency in managing any economic resources that can be utilized. This quantitative research aims to analyze the economic potential of Islamic boarding schools. Data collection methods involve questionnaires and direct observations. The research results indicate that 68% of the surveyed Islamic boarding schools have land available for business development, while 32% state that the existing land is limited for such purposes. Regarding financial aspects, out of the 34 surveyed boarding schools, 68% express a lack of funds or capital for business development, 23% have already secured funding, and 9% are uncertain.